Melt Events in A Nascent Mantle Wedge: Implication from the Luobusa Ophiolite, Tibet. (31st May 2019) - ZHANG, Pengfei; ZHOU, Meifu; MALPAS, John; ROBINSON, Paul
Abstract: The compositions of minerals and whole rocks of the Luobusa ophiolite in South Tibet, a fragment of Neo‐Tethyan forearc lithosphere, is used to investigate the magmatic evolution of nascent mantle wedges in newly‐initiated subduction zones. Clinopyroxenes in the Luobusa peridotites all have diopsidic compositions, and their Al2 O3 contents vary from ∼ 2% in the dunites and refractory harzburgites to 2‐4% in the cpx‐bearing harzburgites. The REE of clinopyroxenes in the harzburgites have left‐sloping patterns with contents comparable to those in abyssal peridotites that have experienced 5‐15% partial melting. Chromites in the Luobusa chromitites have the highest Cr#s (∼ 80) and TiO2 contents (0.1‐0.2%), and those in the cpx‐bearing harzburgites have the lowest Cr#s (20‐60) and TiO2 contents (0‐0.1%), whereas those in refractory harzburgites and dunites have intermediate compositions. Cpx‐bearing and refractory harzburgites show spoon‐and U‐shaped REE patterns, respectively, and their HREE distribution patterns suggest at least 15%‐ 20% partial melting. The REE patterns of dunites and high‐Cr chromitites vary from spoon‐ to U‐shaped and require 15‐30% partial melting in their mantle sources to produce their parental melts. Our dataset reveals that the nascent Luobusa mantle wedge was first infiltrated by slab‐derived fluids and later refertilized by transitional lava‐like melts, resulting in cpx‐bearing harzburgites. Partial melting in the deeper cpx‐bearing mantle generated high‐Ca boninitic to arc picritic melts, which interacted with the peridotites in the uppermost mantle to generate high‐Cr chromitites, dunites and some refractory harzburgites. Lithological variation from cpx‐bearing to refractory harzburgites in forearc ophiolites is the result of multi‐stage melt events rather than increasing degrees of partial melting. Intermittent slab rollback during subduction initiation induces asthenospheric upwelling and high heat flux in nascent mantle wedges. Elevated geothermal gradients play a more important role than slab dehydration in triggering Mg‐rich magmatism in newly‐initiated subduction zones.